Fine-scale Microbial Communities Associated with Manganese Nodules in Deep-sea Sediment of the Korea Deep Ocean Study Area in the Northeast Equatorial Pacific - Cho, Hyeyoun; Kim, Kyeong-Hong; Son, Seung Kyu; Hyun, Jung-Ho (Ocean science journal, 2018)
Despite its potential significance for industrial utilization, any activities associated with the mining of manganese (Mn) nodules might have substantial impacts on benthic ecosystems. Because microorganisms respond quickly to changing environmental conditions, a study of microbial communities provides a relevant proxy to assess possible changes in benthic ecosystems associated with mining activities. We investigated fine-scale microbial community composition and diversity inside and on the surface of Mn nodules and in nearby deep-sea sediments in the Korea Deep Ocean Study (KODOS) area located in the Clarion-Clipperton Fracture Zone (CCFZ) of the northeast equatorial Pacific. Although microbial cell density was lower within nodules (3.21 × 10 6 cells g -1 ) than in sediment (2.14 × 10 8 cells g -1 ), nodules provided a unique habitat for microorganisms. Manganese-oxidizing bacteria including Hyphomicrobium and Aurantimonas in Alphaproteobacteria and Marinobacter in Gammaproteobacteria were abundant in nodules, which implied that these bacteria play a significant role in nodule formation. In contrast, Idiomarina in Gammaproteobacteria and Erythrobacter and Sulfitobacter in Alphaproteobacteria were abundant in sediments. Meanwhile, Thaumarchaeota , a phylum that consists of ammonia-oxidizing chemolithoautotrophs, were the predominant archaeal group both in nodules and sediment. Overall, microbial communities in Mn nodules were unique compared to those observed in sediments. Furthermore, the phylogenetic composition of microorganisms in the KODOS area was distinguishable from that in the nodule provinces claimed by China and Germany in the CCFZ and nodule fields in the central South Pacific Gyre, respectively.